Pendampingan Pembelajaran Bahasa Inggris kepada Siswa Kelas VI MI Mambaul Ulum Banjarejo Pagelaran Malang - Mulis, Mulis (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
This English learning assistance was carried out at MI Mambaul Ulum Banjarejo because at that school English was not practiced (not included in the curriculum) as a general lesson or Mulok. The purpose of this English learning assistance is to provide basic knowledge of English. The learning assistance method used is drilling. In this mentoring activity, there are two skills tests as evaluation material, namely in the middle of the mentoring implementation and at the end of the mentoring meeting. In the end, it was found that based on the scores obtained in the final test of the material presented, there were differences in mastery of the basic material in English; low, fair, and medium